(untitled) (Journal of Educational Sciences, 2017)
In article substantiation of the key information and communication competence modern teacher of foreign language in the framework of the three components,general pedagogical information and communication competence general pedagogical information-communication competence, subject and pedagogical competence. The paper deals with the formation of professional consciousness of the teacher of a foreign language in the course of methodical preparation is closely intertwined with the professional and personal development of the teacher in the conditions of informatization of higher education. The concept of becoming a professional activity in the form of professional work of teacher models. The paper deals with teacher professional priorities, values, the trajectory of selfeducation, self-development and professional self-determination in the profession of the teacher of a foreign language. The article proposes to consider the modern information and communication technology, the advantages of the use of information and communication technologies in teaching foreign languages, as well as the main approaches to learning, the implementation of which comes through the use of information and communication technologies. The necessity of the application of the chain “school-high school” approaches for the effective implementation of information and communication technologies. The concept of learning a foreign language for specific purposes – LSP, foreign language training for academic purposes – LAP. This article provides a list of tasks information and learning environment for the study of a foreign language.